Political economy during the Democrat Party era and Turkey’s development efforts - Tarım, Emre (My University, 2006)
DEMOKRAT PARTİ DÖNEMİNDE EKONOMİ POLİTİKA VE TÜRKİYE’NİN KALKINMA ÇABALARI Türkiye’de çok partili sisteme geçişten dört yıl sonra 1950 yılında iktidara gelen Demokrat Parti, 27 Mayıs 1960’a kadar iktidarda kalmıştır. Bu dönemde Türkiye çevre ülke özelliklerini sürdürmeye devam ederken, kapitalist dünya-ekonomisinde yaşanan genişleme sürecine paralel olarak, DP iktidarının ilk yılları yüksek büyüme ve yatırım oranları yakalamıştır. 1953 yılından sonra Türkiye’nin ihraç ürünleri alehine değişen ticaret hadleri ve tarım üretiminde yaşanan sıkıntılar DP’yi tedrici önlemler almaya iterken, bu önlemler yeni bir sermaye birikim modelinin temellerini atmıştır. Bu çalışmada Demokrat Parti döneminde ekonomide yaşanan gelişmeler, sermaye birikim modelinde yaşanan değişimler çerçevesinde Dünya Sistemleri Yaklaşımı kullanılarak ve inceleme Osmanlı’nın son dönemlerine kadar geri götürülerek ele alınmıştır. Türkiye’nin kapitalist dünya-ekonomisi içindeki konumunun ve Türkiye’deki sermaye sınıfı içindeki farklı grupların durumlarının incelenen dönemde çeşitli sermaye birikim modellerin benimsenmesi arkasında yatan etmenler olduğu gösterilmiştir

POLITICAL ECONOMY DURING THE DEMOCRAT PARTY ERA AND TURKEY’S DEVELOPMENT EFFORTS Four years after the transition to multi-party system in Turkey, Democrat Party came to power in 1950, and remained in power until 27 May, 1960. While Turkey continued to exhibit the features of a peripheral country in that period, the early years of the DP era witnessed high growth and investment rates in parallel to the expansion in the capitalist world-economy. As the deterioration in the terms of trade for Turkish exports and difficulties faced in agriculture sector after 1953 forced DP governments to take temporary measures, those measures laid down the foundations of a new capital accumulation model. In this study, events in the economy during the Democrat Party era are analyzed according to the changes in capital accumulation model by employing the World-Systems Approach, and stretching the analysis back to the late Ottoman years. It is demonstrated that the Turkey’s status within the capitalist world-economy and the constellations within the capitalist class in Turkey are the factors behind designation of various capital accumulation models in the analyzed period.
Keywords: Demokrat Parti; Ekonomi Politikası_Türkiye; Ekonomik Gelişim_Türkiye